Student Dropout in Technological Higher Education Institutions (Docentes 2.0 Journal, 2025)
In recent years, the phenomenon of student dropout in technological higher education institutions has become a growing concern due to its significant social, economic, and educational implications. The primary objective was to conduct a bibliometric analysis of the scientific literature related to this topic, utilizing the PRISMA method in the Scopus database to evaluate trends, prominent authors, and gaps in the existing literature. The research is grounded in a positivist paradigm, employing a systematic method, descriptive narrative design, bibliographic documentary approach, and a cross-sectional design. The analysis included 429 relevant studies identified using specific keywords. Tools such as VOSviewer and RStudio were used for data visualization and analysis, highlighting the temporal evolution of publications, collaborative networks, and thematic clusters. The results showed a sustained increase in academic production since 2015, highlighting themes associated with institutional, socioeconomic, academic, and psychological factors. The findings emphasized the importance of predictive models and early interventions in student retention, also identifying gaps related to cultural factors in developing regions. Thematic maps were generated that reflected key areas of interdisciplinary research. In conclusion, the study provided a comprehensive overview of the trends and factors associated with student dropout, offering a basis for designing inclusive and effective strategies to promote retention in technological higher education institutions. This analysis represents a significant contribution for researchers and educational policymakers interested in mitigating this phenomenon.
Keywords: Academic dropout; higher technological education institutions; bibliometric study; university persistence; socioeconomic determinants